Позиция ЕС относительно неподписания Украиной Соглашения об Ассоциации в 2013 году как предпосылка украинского кризиса - Сорока, Светлана (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2019)
It took the European Union several years to negotiate the Association Agreement with Ukraine, the signing of which was planned for November 2013. Although the Agreement might have had an adverse impact on the Ukrainian economy and society, the government pursued European integration and did not stress these aspects. The Europe-oriented standpoint of President Victor Yanukovych secured support from the majority of Ukrainians. The refusal to sign the Association Agreement triggered social outrage, a sentiment encouraged by the European Union (which was interested in bringing Ukraine into the EU’s sphere of influence). In this way, harsh criticism from the EU of Ukraine’s failure to sign the Agreement became the precursor to the Ukrainian crisis which subsequently ensued.